THE PHYSICAL MODEL FOR AN ORGANIZATION: SIMILAR ASPECTS BETWEEN "ATOM'' AND "ORGANIZATION'' (JOURNAL OF ADVANCES IN PHYSICS, 2017)
In this paper we claim that there exist some similar aspects between "atom'', as a typical physical system, and its counterpart "organization'' as a social system. These similar aspects have been shown by comparison between employees with electrons, board of directors with nucleus, dismissal with photoelectric effect, and organizational restructuring with nuclear reaction.